The Musyawarah Guru Mata Pelajaran Forum and Its Roles in Improving the Professionalism of High School English Teachers - Ambo Dalle; Darmawati Darmawati (Universitas Jambi, Indonesia, 2022)
This study aimed to examine the roles of The Musyawarah Guru Mata Pelajaran (MGMP) in improving the professionalism of high school English teachers in South Sulawesi, Indonesia. The MGMP Forum has been established and operated in nearly every district in South Sulawesi. It was to improve the quality of education in schools, and a means of fostering teacher professionalism is frequently insufficient. This study used a generic qualitative approach. It was selected based on the objectives, which was a description of the reactions of each participant and administrator to the English MGMP Forum with a focus on their knowledge and abilities regarding the theoretical and philosophical foundations of English subjects after participating in the program. According to the findings of our research, the MGMP of English instructors in Parepare City, South Sulawesi, has been able to take positive action. It might be witnessed in at least three ways: boosting the efficacy of English teacher learning, their creativity and talents, and their knowledge and understanding.